ABOUT THREE CATACLYSMIC VARIABLE STARS - Klabukova, A. V. (Одеські астрономічні публікації, 2017)
In order to detect the new outbursts of the three cataclysmic variable TV Crv, NSV 1775, NSV 895, their positions was scanned on the plates of the Odessa collection of the sky service obtained for the period 1958 - 1988. The new outbursts were detected for stars TV Crv, NSV 1725.